1978
DOI: 10.1038/sc.1978.29
|View full text |Cite
|
Sign up to set email alerts
|

The use of operant conditioning techniques in the respiratory rehabilitation of the tetraplegic

Abstract: Abstract. This paper discusses the development of a pilot project in respiratory rehabili tation as part of the total rehabilitation of the tetraplegic and high paraplegic. The prin ciples of neuromuscular exercise and of behaviouristic psychology introduce the subject of operant learning in the rehabilitation setting. Incentive spirometry is described as the basic element in the development of a respiratory rehabilitation programme. The pre liminary results are analysed and a recommendation made that such a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In a cohort with retrospective control study, McMichan and colleagues (1980) demonstrated that a protocol intended to prevent or reduce pulmonary secretions in the ICU decreased mortality, pulmonary complications, and the need for mechanical ventilation. Cheshire and Flack (1978) similarly undertook an incentive spirometry program and demonstrated that with this strategy large improvements in vital capacity could be achieved although this study lacked a control arm. Sugarman (1985) undertook vigorous pulmonary therapy to prevent and treat atelectasis and found that this resulted in prompt normalization of chest x-ray findings and clinical improvement.…”
mentioning
confidence: 99%
“…In a cohort with retrospective control study, McMichan and colleagues (1980) demonstrated that a protocol intended to prevent or reduce pulmonary secretions in the ICU decreased mortality, pulmonary complications, and the need for mechanical ventilation. Cheshire and Flack (1978) similarly undertook an incentive spirometry program and demonstrated that with this strategy large improvements in vital capacity could be achieved although this study lacked a control arm. Sugarman (1985) undertook vigorous pulmonary therapy to prevent and treat atelectasis and found that this resulted in prompt normalization of chest x-ray findings and clinical improvement.…”
mentioning
confidence: 99%
“…(self help). Cheshire and Flack (1978) remarked in a paper on respiratory rehabilitation of the tetraplegic that such a patient has had an overwhelming physical and psychological injury and that the future appears to have nothing but gloom and dependence to offer. To break through this barrier of defeat, the patient often has an urgent need for something which will give him an early obvious visible or tangible success.…”
Section: Introductionmentioning
confidence: 99%